The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.9745/ghsp-d-17-00440
|View full text |Cite|
|
Sign up to set email alerts
|

Increasing Contraceptive Use Among Young Married Couples in Bihar, India: Evidence From a Decade of Implementation of the PRACHAR Project

Abstract: Critical program elements to improving voluntary contraceptive use among married youth included: (1) use of a socioecological intervention model of behavior change; (2) engaging both women and men; and (3) calibrating interventions to different moments in the life cycle of adolescents and youth. Trade-offs between intensive NGO-led models and less intensive government-led models occurred in effectiveness, scale of interventions, and sustained behavior changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…Evidence of community-based multi-component approaches consisting of counseling and life-skills training of young married women, and their husbands, family and community members as well as capacity building of health workers have been showing promising effectiveness in increasing contraceptive use and delaying pregnancy in resource-constrained settings [31, 32]. Recent findings from a decade of the PRACHAR Project in India, showed that a gender-synchronized intervention tailored to specific life stages and based on a socioecological model approach was effective in sustain behavioral change efforts to voluntary increase contraceptive use among young married couples in a conservative area [33]. However, much of the existing evidence comes from small-scale research studies and projects with limitations in their methodology and evaluation design [1, 31].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of community-based multi-component approaches consisting of counseling and life-skills training of young married women, and their husbands, family and community members as well as capacity building of health workers have been showing promising effectiveness in increasing contraceptive use and delaying pregnancy in resource-constrained settings [31, 32]. Recent findings from a decade of the PRACHAR Project in India, showed that a gender-synchronized intervention tailored to specific life stages and based on a socioecological model approach was effective in sustain behavioral change efforts to voluntary increase contraceptive use among young married couples in a conservative area [33]. However, much of the existing evidence comes from small-scale research studies and projects with limitations in their methodology and evaluation design [1, 31].…”
Section: Discussionmentioning
confidence: 99%
“…In developing country little published evidence about married young womenand their partners to address the social and behavioral constraints to contraceptive use. So it is important to learn from the few rigorously documented and evaluated projects that have worked with married young women (13). Overall, only 52.9% of the women in were using a modern contraceptive method globally, but coverage varied greatly.…”
Section: Introductionmentioning
confidence: 99%
“…In developing country little published evidence about married young women and their partners to address the social and behavioral constraints to contraceptive use. So it is important to learn from the few rigorously documented and evaluated projects that have worked with married young women (13). Overall, only 52.9% of the women were using a modern contraceptive method, but coverage varied greatly.…”
Section: Introductionmentioning
confidence: 99%